THE MODERN-DAY SIGNIFICANCE OF THE YOUNG TURKS’ TRIALS: 1919-1921 - Anumyan, Meline (Armenian Folia Anglistika, 2025)
During the past years in the historiography of the Armenian Genocide increased attention has been focused on the fact that the policy of the Ittihatists and the Ottoman Empire to annihilate the Armenians was condemned in 1919-21 by the Extraordinary Military Tribunal through sentences rendered in more than 60 trials. All those judicial cases arose on the basis of charges for deporting and massacring Armenians of the Ottoman Empire during WWI, which served as a basis for the trial of the Young Turks party and government members during the months of April-June, 1919. Those cases were not only the charges for creating the Special Organization, which played a crucial role in carrying out the deportation, annihilation and Genocide of Armenians, but also for drawing the country into the war. In fact, there was no substantiated reason, enabling wartime profiteering and black market activities, and risking the country’s security. Additionally, research on these trials is important for the affirmation of the facts about the Genocide of Armenians. The 1919-1921 trial sessions for the deportations and massacres as well as the testimonies of witnesses and defendants, the encrypted telegrams and especially the final verdicts contained important information about the mechanism implemented in the Genocide of Armenians.